Bujang Tuha: Konstruksi Sosial Terhadap Perempuan Lambat Menikah di Desa Jelapat Kabupaten Barito Kuala - Aulia; Hidayah, Sri (Prodi Sosiologi FISIP ULM, 2024)
Women who are slow to marry in Jelapat Village, Barito Kuala Regency, are always in the spotlight and are discussed. This study aims to analyze the community's views on women who are slow to marry, as well as the reasons that make women decide to marry slowly. This research uses a descriptive qualitative method. The research data is based on social facts obtained through participant observation, in-depth interviews and documentation. The implementation time of this research was in May - September 2023. The data analysis technique used an interactive model, which consists of data collection, data reduction, and data presentation. The results of the study show that the view of women who are slow to marry is influenced by previous thoughts that assume that if a woman is an adult then she is required to get married quickly. The definition of adulthood according to the community does not refer to a certain age, but is seen from the conditions within the woman, namely being able to live independently, for example being able to wash clothes and dishes, clean the house, get a job, and not depend on her parents. Women who decide to marry late due to various considerations will receive negative labeling from the community because they are considered to violate the values and norms that already exist in society. Women who are slow to marry are usually scorned, ridiculed and labeled as bujang tuha, slow to marry, too choosy and unattractive. This kind of thinking is a preconceived social construction that prevails in society. It is important that the scorn, ridicule and labeling of women who are slow to marry stop because it can be mentally damaging to a woman.